RANCANG BANGUN SISTEM MONITORING DAYA PADA GENERATOR SINKRON MENGGUNAKAN DATA LOGGER BERBASIS ARDUINO - Asriadi Asriadi; Tan Suryani Sollu (Foristek, 2020)
Utilization of synchronous generators on micro-hydro Power plant (PLTMH) need direct monitoring with some parameters such as voltage and current. From the results of the monitoring, the information can be obtained whether the synchronous generator installation is appropriate and produce the expected output power. In some studies, the results of current and voltage measurements are still done by manual use of multimeter, so that the data obtained can not be recorded continuously. The purpose of this research is to create a monitoring system on synchronous generators using arduino-based data logger. Monitoring system using data logger is equipped with timing system. Based on the research that has been done can be concluded that the monitoring system on synchronous generators using arduino-based data logger can record current, voltage, and power in real time resulting from generator performance and then record or save the data into the form of CSV file (comma separated values) every 2 seconds into the micro SD and the data can be displayed through Microsoft Office software namely Microsoft Excel.